Risk factors and prognostic analysis of right ventricular dysfunction after lung resection for NSCLC - Tan, Xilun; Tao, Jing; Zhang, Qin; Li, Xiang; Wang, Jia; Song, Hao; Zhou, Yanni; Wang, Sihan; Cheng, Jun; Wang, Ming (Frontiers in Oncology, 2024)
Objectives Lung cancer is the leading cause of cancer death, and 80–85% of all lung cancer cases are non-small cell lung cancer (NSCLC). Surgical resection is the standard treatment for early-stage NSCLC. However, lung resection, a surgical procedure, can result in complications and increased mortality. Recent studies have shown a significant correlation between complications after lung resection and right ventricular dysfunction. Methods Transthoracic echocardiography-derived right ventricular-pulmonary artery coupling (RV-PAC) was utilized to assess right ventricular function in these patients. Multivariate logistic regression analysis was also conducted to assess risk factors independently associated with RV-PA uncoupling. The 3- and 5-year cumulative survival rates were estimated with Kaplan-Meier curves, and differences between groups were analyzed using the Mantel-Cox log-rank test. Results RV-PA uncoupling was defined as a TAPSE/PASP value < 0.67 mm/mm Hg according to spline analysis. The results of multivariable logistic regression analysis indicated that diabetes is an independent risk factor for right ventricular dysfunction after lung resection in patients with NSCLC. Kaplan-Meier analysis revealed a significant decrease in the survival rate of patients with RV-PA uncoupling at both the 3-year follow-up (73% vs 40%, p < 0.001) and 5-year follow-up (64% vs 37%, p < 0.001). Conclusions After lung resection for NSCLC, the patient’s right ventricular function predicts prognosis. Patients with right ventricular dysfunction, particularly those with diabetes mellitus, have a worse prognosis. It is crucial to actively prevent and correct risk factors to reduce the mortality rate in these patients.